FORMULATIONS GEL OF TUNA BONE COLLAGEN (Thunnus albacares) WITH HPMC AS A GELLING AGENT - ari widayanti; Desti Ayu Fauziah; Naniek Setiadi Radjab (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
Tuna’s collagen may be applied to burns at 2%. To provide convenience in use it was made in drug form gel. HPMC is used as a gelling agent because it can form a gel that is clear and netral and has a viscosity that is stable in a long periode. This study aims to determine the effect of increase in the concentration of HPMC as a gelling agent in the gel formula. at a concentration of 3%, 4%, 5%, 6%, 7%. The resulting gel is then evaluated by the organoleptic test, homogeneity test, pH test, viscosity test, centrifugation test, and freeze thaw test. Result of statistical analysis ANOVA one way to test the viscosity of the significant difference in each formula. Based on the result of this study concluded that the increased concentration of HPMC as a gelling agent can increase the viscosity of bone collagen gel tuna.